1999
DOI: 10.1046/j.1365-2249.1999.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase is expressed in joints of goats in the late stage of infection with caprine arthritis encephalitis virus

Abstract: SUMMARYWe have studied the expression of the inducible form of nitric oxide synthase (iNOS) in joints of goats infected with the caprine arthritis encephalitis virus (CAEV). Nitric oxide generated by iNOS is thought to play an important role in the pathogenesis of various types of arthritis, especially rheumatoid arthritis (RA) in humans. Surprisingly, iNOS immunoreactivity was found only in joints of long-term infected goats with severe clinical arthritis, whereas-despite the presence of high numbers of infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…23 Moreover, in affected joints of goats with arthritis, iNOS-expressing cells were CD68-and major histocompatibility complex II (MHCII) -negative and thought to be fibroblast-like synoviocytes. 23 It is possible that the spindloid cells exhibiting iNOS immunoreactivity in the present study were fibroblasts. Cells with similar morphology have been described in a recent report of iNOS immunoreactivity in bovine granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…23 Moreover, in affected joints of goats with arthritis, iNOS-expressing cells were CD68-and major histocompatibility complex II (MHCII) -negative and thought to be fibroblast-like synoviocytes. 23 It is possible that the spindloid cells exhibiting iNOS immunoreactivity in the present study were fibroblasts. Cells with similar morphology have been described in a recent report of iNOS immunoreactivity in bovine granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several important studies demonstrating involvement of many gene products in SRLV infection and disease [137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,155,156,157,158,159,160,161,162], but these do not specifically relate to individual genetic variants present in sheep. In addition to building understanding of infection and disease, such valuable results prepare the way for further work to address whether such genetic variants exist in small ruminants, and if so, begin developing genetic marker tests.…”
Section: Development Of Genetic Marker Tests For Small Ruminant Lementioning
confidence: 99%
“…In addition, the goat model finds a particular acceptance in Orthopedic Medicine fields 23,24 . Lechner et al 25 reported that goat joint injuries showed similarities to those observed in rheumatoid arthritis in humans.…”
Section: Introductionmentioning
confidence: 92%